Peran Orang Tua Menghadapi School Phobia Pada Anak Usia Pra Sekolah (4-6 Tahun) Di TK Nurul Huda Jabon Mojokerto - Ika Suhartanti (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2019)
Every the first education year, it has problem of school phobia that gets on pra student. This case is emerged, because of inability for children are far from their parents. This research is done to know the roles of parents facing school phobila in pre age school in TK NURUL HUDA Jabon Mojokerto, their roles are as decision maker, social developer, giving safety, role mode, team member with teachers. The method of this research is used descriptive by simple random sampling technique. The amount of sampling is 37 respondents and the collecting data is by closed quistionnaire.the result from quistionnarie data is got tabulation and given score then intrepreted in table. This research is found that some respondents whose negative roler (59,45%) and positive roler (40,54%) are their background education of elementary and their job in ungovernmental. This research can be concluded that the role of parents in facing school phobia are negative or missunderstanding about the problem of scholl phobia that get in pre student of school.however, they need information spared about the solving ways of school phobia to children with giving time intensively in facing some problems about children inside.